(untitled) (Stamford Journal of Microbiology, 2020)
The use of antibiotics in the poultry and livestock industries for the treatment and prevention of infectious diseases, and as growth promoters in poultry feeds has increased worldwide. Such frequent employment of antibiotics may contribute to the development and dissemination of bacterial antibiotic resistance. The present study was an attempt to isolate drug-resistant bacteria and to screen the probability of having residual antibiotics in the poultry feed samples. Therefore, a total of 18 samples inclusive of starter, grower and finisher of two poultry feed brands of reputed Bangladeshi feed companies were collected and subjected to microbiological analysis, antibiogram and agar well diffusion assay. All the samples contained extended numbers of total viable bacteria and fungi in an average of 108 and 107 cfu/g, respectively. Klebsiellaspp., Pseudomonas spp. and Bacillus spp. were predominantly present in the tested samples. E. coli and Vibrio spp. were also found in most of the samples. Most isolates have been determined to be multidrug-resistant. All the isolates showed resistance against Cefuroxime. Penicillin resistance was found in most of the isolates in greater proportion. Higher rate of resistance was evident against Novobiocin, Cephradine and Rifampicin. However, the bacterial isolates showed sensitivity to Tobramycin, Nalidixic acid and Neomycin. The poultry feed samples, especially starter and finisher of both brands noticeably had significant antimicrobial activity against the laboratory isolates indicative of the probable presence of residual antibiotics which might be used as supplements in the poultry feed samples. Stamford Journal of Microbiology, Vol.10 (1) 2020: 30-34